2023
DOI: 10.1111/jbl.12325
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain and operations management on the TMT: A study of recall propensity

Abstract: This study investigates the drivers of product quality failures as manifested through recalls. More specifically, this research develops theory regarding supply chain and operations management (SCOM) representation in organizational top management teams (TMT) and this representation's association with the frequency of recalls, the type of recalls, and the severity of recalls. The moderating effect of both recent and historical organizational recall knowledge is also explored. This study uses unique data sets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…This study contributes to operations strategy research by conceptualizing the BoD as a tool to co‐opt supply chain partners and generate relational rents. In so doing, we build on prior work at the intersection of organizational upper echelons and OSCM that has shown the value of prioritizing operations and supply chain management at a strategic level (e.g., Hendricks et al, 2015; Kumar & Paraskevas, 2018; Paraskevas et al, 2023; Roh et al, 2016) and leadership connections to supply chain partner firms (Ambulkar et al, 2023; Bommaraju et al, 2019; Potter & Paulraj, 2020). We extend this stream by evaluating the performance implications when sourcing a board member directly from a supply chain partner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study contributes to operations strategy research by conceptualizing the BoD as a tool to co‐opt supply chain partners and generate relational rents. In so doing, we build on prior work at the intersection of organizational upper echelons and OSCM that has shown the value of prioritizing operations and supply chain management at a strategic level (e.g., Hendricks et al, 2015; Kumar & Paraskevas, 2018; Paraskevas et al, 2023; Roh et al, 2016) and leadership connections to supply chain partner firms (Ambulkar et al, 2023; Bommaraju et al, 2019; Potter & Paulraj, 2020). We extend this stream by evaluating the performance implications when sourcing a board member directly from a supply chain partner.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research further examined the role of individual-level characteristics of executives in the TMT. For example, Kumar and Paraskevas (2018) and Paraskevas et al (2023) found that TMTs comprised of executives with prior work experience in supply chain management are more likely to pursue pro-environmental strategies and implement product recalls, respectively. Mayo et al (2022) similarly related organizational leadership to major operational decisions, finding that CEO tenure decreased the likelihood of product recalls.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The final four manuscripts are diverse in motivation, but all have important L&SCM strategy considerations. First, Paraskevas et al (2023) present, "Supply Chain and Operations Management on the TMT: A Study of Recall Frequency". Top management teams are becoming more involved in L&SCM, so this is a very timely study.…”
Section: Summary Of the Issuementioning
confidence: 99%